O modelo expressivo-colaborativo: uma alternativa feminista à ética tradicional - Possebon, Lúrian (2017)
This paper presents an alternative perspective to the tradicional approach to ethics, based on a feminist ethics. The expressive-collaborative model, as conceived by Margaret Urban Walker, takes on the prior discussion realized by authors of the so called “care ethics”, and redirects its most important insights into a broader context, where not only the experiences of “women” is taken into account, but also those of many “others” that are usually neglected by such tradicional moral theories. For this new model, Walker emphasizes the role of comprehending the moral understandings at stake in the moral community, a task that can be accomplished if we follow the trail of the distribution of responsibilities in such community. In doing so, we have to consider that what is propagated as “knowledge” have strong influence in the ways moral and social arrengements are built, and therefore, in how responsibilities are divided between members of the community. Walker then provides a moral epistemology that sees the production and dissemination of knowledge as a communal practice, and links this naturalized approach with moral practices and social arrengements. The prior concern of this model is, in this sense, metaethical (ou methaetic?): it wants to broaden the notion of what ethics is for, in a way that includes moral experiences of real people in real life, at the same time that provides tools to analyze moral and social arrengements, and the possibility of criticism of some practices that are abusive or oppressive since it provides an account for moral justification. So, at the same time that Walker’s work is about new ways of understanding the meaning and job of ethics and its theorists, it is also directed to the community itself, once it gives valuable insights into the ways moral understandings are entrenched with social, political and epistemological practices, as well as to the meaning and purpose of a moral community itself. Besides these tasks, Walker still indicates paths for reparations after wrongdoins that includes the right to tell the truth – and to be heard – as a fundamental component for a full moral agency, in which the narratives are powerfull resources, as showed through several studies and reports of thuth comissions elaborated in the wake of periods of gross violations of human rights.